Сезонные изменения численности и видового богатства раковинных амеб (Testacealobosea, Testaceafilosea) в р. Гуйва (бассейн Днепра) - Алпатова, О.Н. (Вестник зоологии, 2010)
Приведены результаты исследования сезонных изменений на протяжении 2008–2009 гг. численности и видового богатства раковинных амеб в реке Гуйва. Максимальное видовое богатство и количественное развитие наблюдалось в июне. Установлена достоверная зависимость численности и видового богатства раковинных амеб от концентрации растворенного в воде кислорода и органических веществ, а также численности от температуры. За период исследования обнаружены 48 видов и подвидов тестацей. Data on the seasonal changes of abundance and species richness of testate amoebae species and subspecies in Gujva River during 2008 and 2009 years are presented in the article. The maximal quantitative and qualitative development of testate amoebae was observed in June. The significant relations between amoebae abundance are with temperature of water, dissolved organic matter and dissolved oxygen on the one hand and between species richness of amoebae and dissolved organic matter and dissolved oxygen on the other hand were found. During the period of investigation 48 species and subspecies of testate amoebae were found.